Automating a large library in Nigeria: the story so far (1997)
The University of Ibadan library is the first largest library to automate its library services in Nigeria. It is now a focal point for library automation in the country. Highlights the span of library automation in this library and also reflects the impact of the world bank book project started in 1991 in research and teaching in the university.